The sparkle factory the design and craft of Tarina's fashion jewelry and accessories - Tarantino, Tarina 1968- (Philadelphia Running Press, 2013)
Tarina shares her personal story of how she became a top fashion jewelry and accessories designer and offers tips on how to make some of her most popular pieces.
Introduction: Sparkle is a state of mind! -- History -- Design and inspiration -- Necklaces -- Bracelets -- Earrings -- Rings -- Hair accessories -- Other accessories -- Wearing jewelry -- Your jewelry closet.
Keywords: Jewelry making; Handicraft